Radiation-hygienic characteristics and sanitary condition of the territories of the Globus-3 and the Quartz-2 peaceful nuclear explosions in the Komi Republic - K. V. Varfolomeeva; K. A. Sednev; A. M. Biblin; S. A. Ivanov; S. A. Zelentsova; V. S. Repin; A. G. Georgieva (Радиационная гигиена)
Introduction: Monitoring the level of radioactive contamination, especially the tritium content in water sources, as an indicator of potential releases of man-made radionuclides from radioactive waste storage areas formed as a result of peaceful nuclear explosions, is crucial for ensuring radiation safety. It allows for a prompt response to emerging risks, minimizing negative consequences for the environment and public health.   The purpose of this study was to assess the radiation-hygienic condition of the sites of peaceful nuclear explosions "Globus-3" and "Quartz-2" in the Komi Republic.   Materials and Methods: In July-August 2021, field studies were conducted in the Komi Republic in the territories adjacent to the sites of peaceful nuclear explosions "Globus-3" and "Quartz-2". These studies included measuring the ambient dose equivalent rate, the content of anthropogenic radionuclides in soil, and the specific activity of tritium in water bodies and drinking water sources in the nearest settlements. The ambient dose equivalent rate was measured using an MKG-AT1321 spectrometer. Identification of gamma-emitting radionuclides on the ground was carried out using a scintillation portable gamma-spectrometer MKSP-01. The specific activity of tritium in water samples was determined using a liquid scintillation spectrometer "Quantulus-1220."   Results and Discussion: The measured ambient dose equivalent rate of gamma radiation in all surveyed territories corresponded to the natural radiation background: in the territory of the peaceful nuclear explosion "Globus-3," the values ranged from 0.01 to 0.04 μSv/h, and in the territory "Quartz-2," from 0.01 to 0.06 μSv/h. No soil areas contaminated with anthropogenic radionuclides were detected in the investigated territories. The values of tritium specific activity in drinking water samples did not exceed 5.34 Bq/kg, which is significantly lower than the established hygienic standard (7,600 Bq/kg) and corresponded to background values. Additional anthropogenic exposure due to tritium intake with drinking water from centralized water supply systems did not exceed 0.05 µSv/year.   Conclusion: The radiation situation in the areas of peaceful nuclear explosions "Globus-3" and "Quartz-2" meets the requirements of SanPiN 2.6.1.2819-10 and does not create health risks for the local population. However, the unsatisfactory sanitary condition of the protection zones of these facilities was noted. The presented results are of practical importance for future studies and may serve as a basis for bringing the protection zones into compliance with the requirements of paragraph 3.5 of Section 3 of SanPiN 2.6.1.2819-10.